Aiding the interpretation of forensic gait analysis: Development of a features of gait database. Issue 6 (December 2016) - Birch, Ivan; Gwinnett, Claire; Walker, Jeremy
Highlights: Forensic gait analysis has been presented in court for 15 years. Features of gait are class level features. An understanding of the prevalence of features of gait is therefore key. First attempt to generate a database holding reliable data on features of gait Potential to enhance the presentation and interpretation of gait evidence in court